Impact of bariatric surgery on the sexual health of the morbid obese - Estrada, Roberto Eduardo Guerra; Bohorquez, Guillermo David Barros; Burgos, Rosa Angélica Osorio; Mendonça, Matheus Jannuzzi Moreira de; Sabando, Cindy Margoth Mera; Sabando, Ana Julia Mera; Reyes, José Daniel Sierra; Solano, Omar Avendaño (Jour Med Resh and Health Sci, 2022)
Morbid obesity is a multifactorial chronic disease associated with important physical and psychological complications that contribute to reducing life expectancy and worsening its quality. Within its great complexity, it can be a risk factor for sexual dysfunction (DS) in both genders, since it leads to states of secondary hypogonadism in men and hyperandrogenism in women, in such a way that it alters both normal and reproductive sexual activity. One of the most effective tools in the treatment of obesity is Bariatric Surgery (BC) due to the loss of weight that is obtained, therefore, it is expected to have a favorable impact on sexual dysfunction.